Enhancing wheat production- A global perspective - SHARMA, INDU; TYAGI, B S; SINGH, GYANENDRA; VENKATESH, K; GUPTA, O P (The Indian Journal of Agricultural Sciences, 2015)
The world would require around 840 million tonnes of wheat by 2050 from current production level of 642 million tonnes and it has to be achieved with less land and resources through genetic, physiological and agronomic interventions particularly resource conservation technologies. Besides, precision breeding for improving varietal elasticity, new initiatives for climate change monitoring and crop modelling for advance yield forecasts would help in fulfilling future demands. The future strategies to mitigate adverse effects of climatic change, threat of new and emerging diseases, pests and weed flora, including the issue of increased herbicide resistance, deteriorating soil health need to be implemented to enhance genetic yield potential and sustainability. The researchers also need to explore options to increase yield components through photosynthetic capacity and efficiency, introduction of C4 like traits’carbon concentrating mechanism, improving light interception, optimizing spike and canopy photosynthesis in future genotypes. The fast unravelling sequence information under various national and international projects might offer newer opportunities for reinventing wheat as a crop for ensuring food and nutritional security across the globe.